Dielectric properties of (CuO,CaO₂, and BaO)y/CuTl-1223 composites - Mumtaz, M.; Kamran, M.; Nadeem, K.; Jabbar, Abdul; Khan, Nawazish A.; Saleem, Abida; Hussain, S. Tajammul; Kamran, M. (Физика низких температур, 2013)
We synthesized (CuO, CaO₂, and BaO)y/Cu₀,₅Tl₀,₅Ba₂Ca₂Cu₃O₁₀–δ (y = 0, 5%, 10%, 15%) composites by solid-state reaction and characterized by x-ray diffraction, scanning electron microscopy, dc-resistivity, and Fourier transform infrared spectroscopy. Frequency and temperature dependent dielectric properties such as real and imag-inary part of dielectric constant, dielectric loss, and ac-conductivity of these composites are studied by capacitance and conductance measurement as a function of frequency (10 kHz to 10 MHz) and temperature (78 to 300 K). The x-ray diffraction analysis reveals that the characteristic behavior of Cu₀,₅Tl₀,₅Ba₂Ca₂Cu₃O₁₀–δ supercon-ductor phase and its structure is nearly undisturbed by doping of nanoparticles. The scanning electron microsco-py images show the improvement in the intergranular links among the superconducting grains with increasing nanoparticles concentration. Microcracks are healed up with the inclusion of these nanoparticles and superconduct-ing volume fraction is also increased. The dielectric properties of these composites strongly depend upon the fre-quency and temperature. The zero resistivity critical temperature and dielectric properties show opposite trend with the addition of nanoparticles in Cu₀,₅Tl₀,₅Ba₂Ca₂Cu₃O₁₀–δ superconductor matrix.